Hydrogels with Micellar Hydrophobic (Nano)Domains - Pekař, Miloslav (Frontiers in Materials, 2015)
Hydrogels containing hydrophobic domains or nanodomains, especially of the micellar type, are reviewed. Examples of the reasons for introducing hydrophobic domains into hydrophilic gels are given; typology of these materials is introduced. Synthesis routes are exemplified and properties of a variety of such hydrogels in relation with their intended applications are described. Future research needs are identified briefly.